Oncolytic Viruses—Interaction of Virus and Tumor Cells in the Battle to Eliminate Cancer - Howells, Anwen; Marelli, Giulia; Lemoine, Nicholas R.; Wang, Yaohe (Frontiers in Oncology, 2017)
Oncolytic viruses are an emerging treatment option for many cancer types and have recently been the focus of extensive research aiming to develop their therapeutic potential. The ultimate aim is to design a virus which can effectively replicate within the host, specifically target and lyse tumor cells and induce robust, long-lasting tumor-specific immunity. There are a number of viruses which are either naturally tumor-selective or can be modified to specifically target and eliminate tumor cells. This means they are able to infect only tumor cells and healthy tissue remains unharmed. This specificity is imperative in order to reduce the side-effects of oncolytic virotherapy. These viruses can also be modified by various methods including insertion and deletion of specific genes with the aim of improving their efficacy and safety profiles. In this review, we have provided an overview of the various virus species currently being investigated for their oncolytic potential and the positive and negative effects of a multitude of modifications used to increase their infectivity, anti-tumor immunity and treatment safety, in particular focusing on the interaction of tumor cells and oncolytic viruses.